Traditional Urbanism Response to Climate Change Walled City of Jaipur - Sharma, Anjali Krishan (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book focuses on the key contemporary issue of Climate change, constructing the narrative from traditions' of Urbanism through its Axiology and Epistemology. The book is a rich collection of seven chapters and attempts to address each of the aspects and building further for traditional Urbanism. The book further explores the synergies of traditional urbanism for Climate change through climate responsive practices with main thrust on Energy use. The said understanding is validated through the case example of walled city of Jaipur: World Heritage Site 2019. The chapters enumerate how the traditional urbanism of Jaipur was designed that evolved as climate responsive typology for the respective geography.
Traditional urbanism -- Epistemology of traditional urbanism -- Axiology of traditional urbanism -- Engaging traditional urbanism for climate control -- Synergies between traditional urbanism and climate responsive practices -- Designing traditional urbanism of Jaipur -- Climate responsive typology of Jaipur. .
Keywords: Sustainability; Cultural property; Bioclimatology; Architecture; Urban economics; Sustainability; Cultural Heritage; Climate Change Ecology; Architecture; Urban Economics